Turning A Crisis Into An Advantage: (A Study Of Challenges Faced By Media Industry) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The influence of economic depression during late 2000 is  widely experienced across the world and has affected  almost every sector to some extent. The objective of  present paper is to analyze this impact on media industry.  Hereby, the paper will study the different fields in the media  industry; they are – advertising, news and entertainment.  These fields will be studied in a way to understand the  degree of influence of economic crisis that followed in  fiscal year 2008. The research will seek to examine the  efforts put by the industry to overcome the crisis.  Therefore, the paper will look at the growth drivers or the  various mechanisms that were adopted by the respective  media channels.
Keywords: Growth Drivers; Consolidation Period; FDI and FII